Scatter Hoarding by the Central-American Agouti: A Test of Optimal Cache Spacing Theory - Galvez, D.; Kranstauber, G.; R. W. Kays; Jansen, P. A. (Animal Behaviour, 2009)
Optimal cache spacing theory predicts that scatter-hoarding animals store food at a density that balances the gains of reducing cache robbery against the costs of spacing out caches further. We tested the key prediction that cache robbery and cache spacing increase with the economic value of food: the ratio of food to consumer abundance. We quantified cache pilferage and cache spacing by the Central American agouti, Dasyprocta punctata, in the tropical forest of Barro Colorado Island, Panama, across 10 1 ha plots that encompassed a more than100-fold range in the availability of Astrocaryum palm seeds, the agouti's principal food. We found that caches were pilfered at higher rates in plots with lower seed availability, and that agoutis cached seeds further away and into lower densities where seed availability was lower. Food scarcity apparently increased the pressure of food competitors on caches, stimulating agoutis to put more effort into caching seeds to create lower cache densities, fully consistent with theory. We conclude that the optimal cache density depends not only on the nutritional value of food but also on the economic value, which may vary in space as well as time.
Keywords: cache pilferage; camera trapping; Central American agouti; Dasyprocta punctata; food availability; optimal cache spacing; scatter hoarding; Seed dispersal; tropical forest